Answer:
2x^2+14x+5
Step-by-step explanation:
x^2+9x+5x+5
Combine Like Terms:
=2x^2+9x+5x+5
=(2x^2)+(9x+5x)+(5)
=2x^2+14x+5
Answer:
B
Step-by-step explanation:
A. 37 isn't a number sentence
B. 49 + (-12) = 49-12. They're the same thing because 49 minus 12 can also be written as 49 plus negative 12
C. 49 + 12 doesn't equal 49-12
D. 12- 49 = -37 which isn't equivalent to 49-12.
Hope this helps!!!
Answer:
Not enough info for a valid answer.
Step-by-step explanation:
Answer:
y=11
x=-4
Step-by-step explanation:
y =-x+7
2x-5y=-7
insert the first equation into the second like so...
2x+5x-35=-7
Now rearrange...
2x+5x=-7+35
Now solve...
7x=-28
x=-4
Now incert x in any equation...
y=4+7
y=11
Answer:
C
Step-by-step explanation:
Using the rule of radicals
×
⇔ ![\sqrt{ab}](https://tex.z-dn.net/?f=%5Csqrt%7Bab%7D)
Simplifying each radical before combining them.
![\sqrt{45t}](https://tex.z-dn.net/?f=%5Csqrt%7B45t%7D)
=
=
×
= 3![\sqrt{5t}](https://tex.z-dn.net/?f=%5Csqrt%7B5t%7D)
-----------------------------------------------------------------------------
![\sqrt{125t}](https://tex.z-dn.net/?f=%5Csqrt%7B125t%7D)
= ![\sqrt{25(5t)}](https://tex.z-dn.net/?f=%5Csqrt%7B25%285t%29%7D)
=
×
= 5![\sqrt{5t}](https://tex.z-dn.net/?f=%5Csqrt%7B5t%7D)
---------------------------------------------------------------------------
Hence
2(3
) - 3(5![\sqrt{5t}](https://tex.z-dn.net/?f=%5Csqrt%7B5t%7D)
= 6
- 15![\sqrt{5t}](https://tex.z-dn.net/?f=%5Csqrt%7B5t%7D)
= - 9
→ C